Evaluating the potential for transboundary management of marine biodiversity in the Western Indian Ocean. Issue 1 (2nd January 2018) - Levin, Noam; Beger, Maria; Maina, Joseph; McClanahan, Tim; Kark, Salit
ABSTRACT: The economic and socio-political interactions between countries can have major impacts on transboundary conservation decisions and outcomes. Here, we examined for 14 Western Indian Ocean (WIO) continental and island nations the extent of their marine coral reef species, fisheries and marine protected areas (MPAs), in the context of their geopolitical and socio-economic connections. We also examined the role of external countries and organisations in collaboration within the region. We found large variation between the different countries in their protected area size, and management, which result from different interests in establishing the MPAs, ranging from fisheries management, biodiversity conservation to asserting sovereignty claims. Seventy-four per cent of the 154 MPAs in the region belong to island nations; however, the largest MPAs in the WIO were established by European powers, and include Mayotte and Glorioso Islands (France) and Chagos (UK). While the majority of MPAs are managed by individual countries, between-country collaboration within and outside the region is key if the aim is to achieve effective conservation of ecosystems and species across the island and mainland nations in the region. This may be advanced by creating transboundary MPAs and by regional conservation investment by external powers that benefit from the region's resources.